Disparities in Health Information-Seeking Behaviors and Fatalistic Views of Cancer by Sexual Orientation Identity: A Nationally Representative Study of Adults in the United States - Langston, Marvin E. (LGBT Health, 2019)
Purpose: A lack of national data makes it difficult to estimate, but LGB adults appear to have a higher risk of cancer. Although limited research exists to explain the disparity, we aimed to explore potential differences in access to and utilization of health information and in cancer-related beliefs and behaviors. Methods: We used data from the Health Information National Trends Survey 5, Cycle 1 conducted from January 25 through May 5, 2017. Using survey-weighted logistic regression, we explored potential differences in health information-seeking behavior, trusted sources of health care information, engagement with the health care system, awareness of cancer risk factors, cancer fatalism, cancer-related health behaviors, and historical cancer screening between 117 LGB and 2857 heterosexual respondents. Results: LGB respondents were more likely to report looking for information about health or medical topics than heterosexual respondents (adjusted odds ratio [aOR]: 3.12; confidence interval [95% CI]: 1.07–9.06), but less likely to seek health information first from a doctor (aOR: 0.17; 95% CI: 0.06–0.50) after adjusting for age, race, and sex. LGB persons were less likely to report that they trust receiving health or medical information from friends and family and more likely to be worried about getting cancer (aOR: 2.30; 95% CI: 1.04–5.05). Conclusions: Our findings indicate a growing need for the production of tailored cancer prevention and control materials for members of sexual minority groups. More work is needed to understand barriers that LGB populations face in accessing this health information and building informative social support networks.